Assessment of the Quality of Basic and Expanded Resuscitative Measures in a Multifield Hospital (Simulation Course) - A. N. Kuzovlev; S. N. Abdusalamov; K. A. Kuz'michev (Общая реаниматология, 2017)
The survival of patients after the sudden circulatory arrest (SCA) depends not only on immediate onset of resuscitative measures, but also on their quality.The purpose of the study. The purpose is to assess the compliance of basic and expanded resuscitative measures carried out by healthcare providers in hospitals with modern national and international guidelines within the frames of a stimulation course.Materials and Methods. The research was perfomed in a multifield hospital in Moscow, in 2016. It consisted of two phases. During the first phase, within the frames of a simulation course, providers' skills in the cardiopul monary resuscitation (CPR) and chest compression (CC) technique mastership were evaluated. During the second stage, their skills in expanded CPR and ability to work as a part of resuscitation teams were assessed. During the simulation, all team activities were recorded (both audio and video); CC parameters were also registered using a CC pressure control sensor (hereinafter referred to as a sensor) and audiovisual tips. The European Resuscitation Council Guidelines for Resuscitation 2015 were used as reference criteria. The analysis was performed using the ZOLL RescueNet Code Review® software. A statistical analysis was performed using the Statistica 7.0 software (MannWhitney Utest). The data were presented as a mean, median ± 25—75 percentiles (25—75 IQR), minimum and maximum values. The difference was considered significant at P<0.05.Results. Test results of most healthcare providers were unsatisfactory when the CPR was performed without sensors and audiovisual tips: the percentage of target CCs was not more than 10% in 72% of providers (n=18). When the CPR was performed with sensors and audiovisual tips regulating the CC quality, the percentage of target CCs was 65.7%. i.e. it was significantly higher than that during the CPR without the sensor and the tips (P=0.0000). While only one provider was able to perform the target CC without the sensor and the tips (4%), 12 providers were able to do it with the sensor (48%) (P=0.0000). In all resuscitation teams, there was a lack in compliance with the ECR 2015 guidelines for expanded CPR, as well as ineffective team work was revealed. Chest compressions did not comply with recommended parameters; pauses before and after defibrillator discharge were too long. In most cases, there was hyperventilation during the artificial lung ventilation. The safety principle was not followed by one of resuscitation teams during the defibrillation procedure.Conclusion. The obtained data demonstrate that healthcare providers have poor skills in basic and expanded CPR. Therefore, it is important to train and retrain healthcare providers in basic and expanded CPR within the frames of simulation training courses on a regular basis (in accordance with European Resuscitation Council Guidelines for Resuscitation 2015 and National Resuscitation Council). During training, the use of technical means of monitoring of the chest compression quality control in CPR should be warranted. It is important to arrange regular retraining in order to keep the skills uptodate, as well as regular debriefings on the CPR quality after each case of resuscitation measures in a hospital.